Three‐dimensional analysis, modeling, and simulation of the effect of static magnetic fields on neurons. Issue 2 (14th November 2016) - Hashemi, Soheil; Abdolali, Ali
Abstract : The effect of static magnetic fields on neuron function has been studied. None of the possible explanations are decisive or fully consistent with evidence in the literature. Therefore, the purpose of this paper is to examine the different possibilities, for the first time, through a three‐dimensional modeling strategy in an effort to find out which possibility or combination is effective on cell function. A full‐wave analysis was employed to simulate various effects of magnetic fields. The possibilities included force exerted on mobile ions, magnetophoretic force exerted on ions with permeability different from intracellular or extracellular fluids, magnetophoretic force exerted on sensor proteins in ion channels, and magnetophoretic pressure exerted on the membrane and spatial rotation of anisotropic diamagnetic particles. According to the simulations, the last two possibilities are more likely to be effective; therefore, their corresponding equations in this article were formulated to verify the results of the literature experiments. Bioelectromagnetics. 38:128–136, 2017. © 2016 Wiley Periodicals, Inc.